PENGARUH LATIHAN GABUNGAN SUPER GARUDA SHIELD TERHADAP DIPLOMASI PERTAHANAN INDONESIA-TIONGKOK (STUDI KASUS: LAUT NATUNA UTARA) - Ramadhan, Rifky Putra; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to determine and analyze the impact of the Super Garuda Shield Joint Exercise on Indonesia-China defense diplomacy in the North Natuna Sea, a maritime disputed area due to China's overlapping claims within Indonesia's EEZ. The focus of this research is on how Indonesia and the United States engage in the joint exercise and how it can influence bilateral defense diplomacy strategies, including as a political signal of balance of threat against China's claims.. The perspective used is neoliberalism with a state-level analysis, and Stephen Walt's balance of threat theory as the main conceptual framework. This study finds that the Super Garuda Shield Joint Exercise serves as an instrument to enhance Indonesia's defense capabilities and a political signal to balance the Chinese threat, while strengthening its bargaining position in bilateral diplomacy. This role includes increasing military interoperability with the United States, strengthening deterrence in Natuna, and facilitating regional security dialogue. However, various challenges such as Indonesia's pro-Western perception, escalating Chinese activity, and trilateral tensions remain major obstacles. Keywords: Super Garuda Shield, Diplomacy, North Natuna Sea